Johannes Climacus e o pensador subjetivo existente. A categoria trágico-cômica da linguagem indireta - Ana Alice Matiello Coelho (Ideas y Valores)
The article analyzes the assumptions of J. Climacus’ (Kierkegaard) double reflection in order to understand his critique of dialectical-speculative thought. Since that double reflection revisits the concepts of the tragic and the comic, of seriousness and jest, albeit from a different perspective, we can understand the importance of such communication for indirect language, whose objective is to communicate an absolute contradiction.